Professional Review Guide for the CCS Examination - Patricia Schnering;... (Thomson Delmar Learning,PRG Pub., 2007)
The Professional Review Guide for the CCS Examination, 2007 Edition contains: study tips, a comprehensive resource list, a review section with multiple choice coding questions that review a broad range of competencies. This valuable manual also includes coding case studies for coding review for the CCS examination, a mock examination that strives to mirror the CCS Examination. The mock examination includes 60 multiple choice coding questions reviewing a broad range of competencies, 21 medical record coding cases, 11 outpatient records, 5 Ambulatory surgery, 3 emergency room, 3 other, and 10 inpatient records. The appendices include: Official Guidelines for ICD-9-CM Guidelines for Coding and Reporting, Commonly Administered Drugs, Lab values, and a new listing of updated ICD-9-CM coding changes for 2007. Use the book and the Interactive CD-ROM to practice interpreting documentation and applying clinical knowledge in assigning codes to diagnoses and procedures for a variety of patient settings including: Inpatient, Outpatient surgery, Emergency Room, Physician office, and Long term Care